Suitability Evaluation of Site-Level CO2 Geo-Storage in Saline Aquifers of Ying–Qiong Basin, South China Sea - Jin Liao; Cai Li; Qihui Yang; Aixia Sun; Guangze Song; Joaquin Couchot; Aohan Jin; Quanrong Wang (Energies, 2025)
CO2 geo-storage is a promising approach in reducing greenhouse gas emissions and controlling global temperature rise. Although numerous studies have reported that offshore saline aquifers have greater storage potential and safety, current suitability evaluation models for CO2 geo-storage primarily focus on onshore saline aquifers, and site-level evaluations for offshore CO2 geo-storage remain unreported. In this study, we propose a framework to evaluate the site-level offshore CO2 geo-storage suitability with a multi-tiered indicator system, which considers three types of factors: engineering geology, storage potential, and socio-economy. Compared to the onshore CO2 geo-storage suitability evaluation models, the proposed indicator system considers the unique conditions of offshore CO2 geo-storage, including water depth, offshore distance, and distance from drilling platforms. The Analytic Hierarchy Process (AHP) and Fuzzy Comprehensive Evaluation (FCE) methods were integrated and applied to the analysis of the Ying–Qiong Basin, South China Sea. The results indicated that the average suitability score in the Yinggehai Basin (0.762) was higher than that in the Qiongdongnan Basin (0.691). This difference was attributed to more extensive fault development in the Qiongdongnan Basin, suggesting that the Yinggehai Basin is more suitable for CO2 geo-storage. In addition, the DF-I reservoir in the Yinggehai Basin and the BD-A reservoir in the Qiongdongnan Basin were selected as the optimal CO2 geo-storage targets for the two sub-basins, with storage potentials of 1.09 × 108 t and 2.40 × 107 t, respectively. This study advances the methodology for assessing site-level potential of CO2 geo-storage in offshore saline aquifers and provides valuable insights for engineering applications and decision-making in future CO2 geo-storage projects in the Ying–Qiong Basin.